Robust Interlayer Bonding in PLA-TPU Composites via Optimized Overlap 3D Printing - Arriola, Emmanuel; Lopez, Toni Beth; Javate, Joaquin Ronald; Santos, Gil Nonato (International Journal of Research in Interdisciplinary Studies, 2025)
Material extrusion 3D printing has made significant strides, yet challenges remain in seamlessly integrating multiple polymer materials in a single print. This abstract introduces a novel technique that precisely overlaps two polymer materials during the printing process, expanding the capabilities of additive manufacturing. Leveraging advanced control systems to synchronize the deposition of two distinct polymers, this method ensures a seamless transition and strong adhesion between layers. Optimizing material flow rates, temperature profiles, and layer bonding mechanisms is crucial for achieving high-quality prints with enhanced structural integrity and material properties. This approach unlocks possibilities across various industries. For instance, in the automotive sector, it enables the fabrication of lightweight components with tailored mechanical properties, such as reinforced sections overlapped with flexible elastomers for vibration damping. In the medical field, the technique facilitates the creation of complex implants with biocompatible coatings for improved integration and reduced rejection rates. Beyond traditional applications, this technique paves the way for developing functional prototypes, customized products, and advanced composite structures with superior performance characteristics. Through collaborative efforts and continued innovation, this method promises to redefine the boundaries of additive manufacturing and drive the next wave of technological advancement. By enabling the precise deposition of overlapping polymer materials, it significantly enhances the potential of 3D printing technology, offering new solutions to complex manufacturing challenges and contributing to the advancement of various fields.